Proceedings of the 1st International Workshop on Software Engineering for Cognitive Services 2018
DOI: 10.1145/3195555.3195567
|View full text |Cite
|
Sign up to set email alerts
|

Smart conversational agents for reminiscence

Abstract: In this paper we describe the requirements and early system design for a smart conversational agent that can assist older adults in the reminiscence process. The practice of reminiscence has well documented benefits for the mental, social and emotional well-being of older adults. However, the technology support, valuable in many different ways, is still limited in terms of need of co-located human presence, data collection capabilities, and ability to support sustained engagement, thus missing key opportunitie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 33 publications
0
10
0
3
Order By: Relevance
“…Previous research focused on reminiscence as a therapy against dementia have shown the efficacy of information and communication technologies [ 14 ]; in particular, studies addressing the topic of automated reminiscence therapy aim at eliciting reminiscence from the users rather than detecting the presence of reminiscence in everyday life [ 17 , 18 ]. These studies have assumed that reminiscence is elicited in a setting with a human companion (eg, a therapist) or through a digital companion device using the Wizard of Oz technique [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research focused on reminiscence as a therapy against dementia have shown the efficacy of information and communication technologies [ 14 ]; in particular, studies addressing the topic of automated reminiscence therapy aim at eliciting reminiscence from the users rather than detecting the presence of reminiscence in everyday life [ 17 , 18 ]. These studies have assumed that reminiscence is elicited in a setting with a human companion (eg, a therapist) or through a digital companion device using the Wizard of Oz technique [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…They include: Siri (Apple), Alexa (Amazon) and Google Assistant. Conversational interfaces have been studied in a variety of contexts, ranging from: health care [27], aging [31], physical activity [49,8], and for people with an intellectual disability [6].…”
Section: Related Workmentioning
confidence: 99%
“…In line with this approach, PAs have been used to significantly improve episodic memory by using a reminiscing agent to debrief the student following exploration of a virtual world (Nicholas, Van Bergen, & Richards, 2015). Similar to the use of IVAs to assist the elderly to reminisce (Nikitina, Callaioli, & Baez, 2018), PAs could help students with remembering and act as a form of external memory aid that does more than store or retrieve information. Another direction to encourage reflection is the use of teachable agents where the human (co)-learner teaches the agent what to do or provides the agent with answers to its questions (Pareto, 2014).…”
Section: Pedagogy: Vision and New Possibilitiesmentioning
confidence: 99%